2015
DOI: 10.1186/s40842-015-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oxidative stress and haematological indices in patients with diabetes in the Ghanaian population

Abstract: BackgroundPersistent hyperglycaemia is a hallmark of Diabetes Mellitus (DM). It causes increased production of free radicals, especially reactive oxygen species (ROS), — resulting in oxidative stress. Reactive Oxygen Species have been implicated in the development of haematological complications in patients with diabetes. Superoxide Dismutase (SOD) is one of the most effective antioxidant enzyme defense systems against free radicals.MethodsFrom February through May 2014, we assessed the relationship between ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
3
17
0
1
Order By: Relevance
“…These studies present some limitations that should be addressed in future research: in particular, neither potential gender-related differences nor racial disparities in oxidative stress biomarkers have been actively investigated so far; nevertheless, both racial and gender differences in the markers of oxidative stress have been reported [68, 112, 113]. A limitation of many studies is that medications such as statins, β -blockers, angiotensin-converting enzyme inhibitors, and angiotensin receptor blockers which exhibit antioxidant effects were not always analysed as potential confounding factors [114]; a limitation of many studies is that these medications were not always included in the analyses as potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…These studies present some limitations that should be addressed in future research: in particular, neither potential gender-related differences nor racial disparities in oxidative stress biomarkers have been actively investigated so far; nevertheless, both racial and gender differences in the markers of oxidative stress have been reported [68, 112, 113]. A limitation of many studies is that medications such as statins, β -blockers, angiotensin-converting enzyme inhibitors, and angiotensin receptor blockers which exhibit antioxidant effects were not always analysed as potential confounding factors [114]; a limitation of many studies is that these medications were not always included in the analyses as potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Plt levels may also be decreased along with an increased globulin and uric acid level. Additionally, RBCs are particularly sensitive to oxidative stress, which can cause RBC hemolysis [34]. In this work, hematological parameters were also evaluated in PKU patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress caused by an unbalancing between free radical production and the antioxidant defense systems can lead to red blood cell (RBC) dysfunction, platelet destruction, and tissue damage (Asmah et al, 2015). Several epidemiological studies have suggested that prolonged exposure to ELF-EMFs may be linked to an increased risk of childhood cancer, especially leukemia (Koeman et al, 2014; Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%